2023
DOI: 10.1111/pai.14049
|View full text |Cite
|
Sign up to set email alerts
|

From preschool wheezing to asthma: Environmental determinants

Yuhan Xing,
Agnes Sze‐Yin Leung,
Gary Wing‐Kin Wong

Abstract: Wheezing is common among preschool children, representing a group of highly heterogeneous conditions with varying natural history. Several phenotypes of wheezing have been proposed to facilitate the identification of young children who are at risk of subsequent development of asthma. Epidemiological and immunological studies across different populations have revealed the key role of environmental factors in influencing the progression from preschool wheezing to childhood asthma. Significant risk factors includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 106 publications
1
0
0
1
Order By: Relevance
“…The present study found that children residing in the Mpumalanga Highveld region were predominantly impacted by Wheeze Ever, a common symptom of asthma, and also had a history of Asthma Ever, particularly if they attended an urban preschool. The results of our study align with the majority of the existing literature, which consistently demonstrates that residing in rural areas or on farms, being exposed to livestock, and the hygiene hypothesis confer protective advantages against the development of asthma and or symptoms in childhood compared to children residing in urban areas [11,20]. Additionally, our research findings provide support for the notion that children residing in urban areas are more prone to increased exposure and heightened sensitivity to several risk factors associated with asthma and or symptoms [21].…”
Section: Discussionsupporting
confidence: 88%
“…The present study found that children residing in the Mpumalanga Highveld region were predominantly impacted by Wheeze Ever, a common symptom of asthma, and also had a history of Asthma Ever, particularly if they attended an urban preschool. The results of our study align with the majority of the existing literature, which consistently demonstrates that residing in rural areas or on farms, being exposed to livestock, and the hygiene hypothesis confer protective advantages against the development of asthma and or symptoms in childhood compared to children residing in urban areas [11,20]. Additionally, our research findings provide support for the notion that children residing in urban areas are more prone to increased exposure and heightened sensitivity to several risk factors associated with asthma and or symptoms [21].…”
Section: Discussionsupporting
confidence: 88%
“…The risk factors, both genetic and environmental, influencing the progression of preschool wheezing to asthma have been highlighted in previous articles in this series. [1][2][3][4][5] Influences include underlying susceptibility, antenatal, perinatal and postnatal factors. Novel, data-driven methodological approaches that might help to consolidate the data available and aid our understanding of disease progression have also been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Генетические факторы играют значительную роль в риске развития бронхиальной астмы, при этом полногеномные ассоциативные исследования показали, что выявленные генетические варианты объясняют только примерно 9% наследственности астмы, что может быть объяснено повышенной пенетрантностью генотипов предрасположенности к астме, факторами окружающей среды, которые проявляют свое влияние через взаимодействие генов и окружающей среды [7,8,9]. Эти данные перенаправили траекторию исследований основных дескрипторов заболеваний от патомеханистического подхода по симптомам и дисфункции органов к распознаванию патогенетических иммунологических, метаболических путей и поиску валидных биомаркеров [1,10,11,12].…”
unclassified